Bioprospecting aerobic rice (Oryza sativa) and mycorrhizal interaction for nutrient uptake and plant growth - NARWAL, EKTA; ANNAPURNA, K; CHOUDHARY, JAIRAM; DHAKAR, RAJKUMAR; SINGH, Y V (The Indian Journal of Agricultural Sciences, 2021)
With the growing concern of water scarcity in agriculture, aerobic rice (Oryza sativa L.) is a promising mode of cultivation for reducing water use, although the reduced optimal plant growth and yield are major constraints. Arbuscular mycorrhiza (AM) are known to readily colonize rice roots under aerobic conditions, however, the response of upland and lowland rice genotypes has not been investigated. This study was carried out during 2018-19 at ICAR-IARI, New Delhi, using a mycorrhizal consortium and percent colonization was observed to be higher by 58% in upland rice genotypes. AM- upland plants also showed 20% higher plant biomass. AM colonization significantly enhanced rice growth under aerobic conditions, with the upland rice genotypes. Pyari and Satyabhama showed higher response upon AM inoculation. AM colonization increased the total chlorophyll by 54% and the upland rice genotypes showed 51% enhanced nitrogenase activity in their root zones, with highest recorded for Satyabhama. The AM plants showed enhanced activities of nitrate reductase (NR) and glutamine synthetase (GS), and interestingly, the rice genotypes with higher NR and GS (Pyari, Satyabhama) also exhibited more (20%) biomass production and plant N content (36%). Significant varietal differences were recorded in terms of accumulation of antioxidant compounds such as ascorbate, glutathione and proline in AM inoculated plants, which helped to alleviate negative effects of water stress in rice plants under aerobic cultivation.